Core/Shell CdSe/CdS Bone‐Shaped Nanocrystals with a Thick and Anisotropic Shell as Optical Emitters. Issue 1 (14th November 2019) - Castelli, Andrea; Dhanabalan, Balaji; Polovitsyn, Anatolii; Caligiuri, Vincenzo; Di Stasio, Francesco; Scarpellini, Alice; Brescia, Rosaria; Palei, Milan; Martín‐García, Beatriz; Prato, Mirko; Manna, Liberato; Moreels, Iwan; et al.
Abstract: Colloidal core/shell nanocrystals are key materials for optoelectronics, enabling control over essential properties via precise engineering of the shape, thickness, and crystal structure of their shell. Here, the growth protocol for CdS branched nanocrystals is applied on CdSe nanoplatelet seeds and bone‐shaped heterostructures are obtained with a highly anisotropic shell. Surprisingly, the nanoplatelets withstand the high growth temperature of 350 °C and structures with a CdSe nanoplatelet core that is overcoated by a shell of cubic CdS are obtained, on top of which tetrahedral CdS structures with hexagonal lattice are formed. These complex core/shell nanocrystals show a band‐edge emission around 657 nm with a photoluminescence quantum yield of ≈42% in solution, which is also retained in thin films. Interestingly, the nanocrystals manifest simultaneous red and green emission and the relatively long wavelength of the green emission indicates charge recombination at the cubic/hexagonal interface of the CdS shell. The nanocrystal films show amplified spontaneous emission, random lasing, and distributed feedback lasing when the material is deposited on suitable gratings. This work stimulates the design and fabrication of more exotic core/shell heterostructures where charge carrier delocalization, dipole moment, and other optical and electrical properties can be engineered. Abstract : A new type of highly anisotropic core/shell nanocrystals is developed with a shell made of different crystal structures and thickness, and a core that preserve its nanoplatelet geometry despite the high synthesis temperatures. Such complex shape enables double emission, amplified spontaneous emission, random lasing, and distributed feedback lasing, opening new views on engineering optical properties through exotic particle architectures.